EFIKASI DAN KEAMANAN TERAPI SEL PUNCA MESENKIMAL AUTOLOG TERHADAP REGENERASI JANTUNG PASCA INFARK MIOKARD: Systematic Review - Sakhia Syahda Asmara (2021)
Myocardial Infarction (IM) is necrosis of the myocardium due to blood flow decreased or blockage to the heart. The necrosis is followed by tissue remodeling leading to left ventricular dysfunction with an LVEF of less than 50%. Several studies have showed that remodeling can be improved by presenting mesenchymal stem cells via the proposed paracrine mechanism. This systematic review will analyze the safety and efficacy of autologous mesenchymal stem cells in cardiac regeneration after myocardial infarction to lower complications and increase patients' quality of life in the future. Methods: A systematic review was conducted by searching the literatures on the PubMed, Google Scholar, Cochrane, and Science Direct databases, guided by the PRISMA-P 2020 method, and re-selected through the JBI Critical Appraisal Checklist. Results: autologous mesenchymal stem cells could improve heart function, characterized by increased functional and structural parameters. Functional parameters consist of LVEF, LVESV, LVEDV, and WMSI, while structural parameters consist of viability, perfusion, and infarct mass. The efficacy is indicated by an average increase in the functional parameter, namely LVEF of 7.8% with significant increase in four of the eight literatures. In addition, four of the six literatures have a significant improvement on the structural parameters. Mesenchymal stem cells also had a high proportion of safety (89%) with an incidence of MACE (9%) and other mild side effects (2%) out of a total of 145 samples. Conclusion: autologous mesenchymal stem cells are safe and effective for cardiac regeneration after myocardial infarction.